Peningkatan Hasil Belajar Peserta Didik melalui Penerapan Model Pembelajaran Problem Based Learning (PBL) di SMK Negeri 1 Purwosari - Dwi Lindah Permatasari; Sunaryo Sunaryo; Isa Sidharta (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to improve the learning outcomes of class XI students on the material of identification and control of food crop diseases through the application of the Problem Based Learning (PBL) learning model. The research method used is classroom action research (PTK) with the Kemmis and Taggart model which is carried out in two cycles. Each cycle consists of planning, action, observation, and reflection stages. The subjects of the study were class XI ATPH 1 students at SMK Negeri 1 Purwosari. The method of data collection was through learning outcome tests and observation sheets. The results of the study showed that the application of the PBL model can improve students' learning outcomes on the material.